Climate Vulnerability of Australian Seafood Systems: A National Assessment of Exposure and Adaptive Capacity - Stephanie Brodie; Laura K. Blamey; Ana Bugnot; Rodrigo H. Bustamante; Julia L. Blanchard; Lara Buhagiar; Elizabeth A. Fulton; Alistair J. Hobday; Éva E. Plagányi; Anthony J. Richardson; Richard Matear; Skipton N. C. Woolley; et al. (Fisheries Oceanography, 2026)
Marine waters are becoming warmer and acidified and experiencing more intense and longer heatwaves under climate change. These changes are already impacting marine ecosystems and seafood production, which are vital for supporting food security and economic productivity. For Australia, a national‐scale assessment of exposure to climate hazards is needed to support climate‐resilient ecosystem management across one of the world's largest exclusive economic zones. Commercial fishing relies on healthy ecosystems and is one of Australia's most important sectors in terms of cultural identity and regional value. However, Australian fisheries and aquaculture are increasingly exposed to climate‐driven changes in ocean conditions, creating substantial risks for marine ecosystems, seafood production and coastal economies. We assess the exposure of Australia's seafood sector to climate change using high‐resolution climate projections and ecosystem model outputs under three global warming levels (1.5°C, 2°C and 3°C futures). Our findings reveal that the entire Australian exclusive economic zone is exposed, with cumulative exposure highest for regions with a large continental shelf. The biomass available to fisheries is projected to decline. Negative impacts from climate change are generally expected for fisheries and aquaculture production. Despite some evidence of adaptation, uneven adaptive capacity across sectors and jurisdictions presents challenges for climate resilience. This study underscores the urgency of global mitigation efforts to reduce risk, coordinated adaptation strategies, improved coastal hazard modelling and ecological risk assessments to safeguard the future of fisheries and aquaculture industries under climate change.

Marine heatwaves alter shell microbiomes and denitrification capacity: An oyster family-specific response - Giulia Filippini; Ana B. Bugnot; Wayne O'Connor; Paul E. Gribben; Deepa R. Varkey; Ian T. Paulsen; Katherine A. Dafforn (Marine Pollution Bulletin, 2026)

Effects of spatial attributes of oyster reefs on epifaunal assemblages vary at regional scales - Rick C. Leong; Paul E. Gribben; Ezequiel M. Marzinelli; Will F. Figueira; Katherine R. Erickson; Alistair G.B. Poore; Ana B. Bugnot (Marine Environmental Research, 2025)

Interdisciplinary solutions to enable nature-based solutions for coastal protection achieve ecological and engineering outcomes - Alice J. Twomey; Katherine Erickson; Melanie J. Bishop; Kris Boody; David P. Callaghan; Toni Cannard; Catherine E. Lovelock; Mariana Mayer-Pinto; Rebecca L. Morris; Andrew W.M. Pomeroy; Megan I. Saunders; Andy Steven; et al. (Environmental Science & Policy, 2025)

Benthic Processes are an Important Indicator of Eutrophication in Intermittently Open and Closed Lakes and Lagoons - Angus Ferguson; Giulia Filippini; Jaimie Potts; Ana B. Bugnot; Emma L. Johnston; Shivanesh Rao; Jason Ruszczyk; Katherine A. Dafforn (Estuaries and Coasts, 2024)
Intermittently open and closed lakes and lagoons (ICOLLs) are globally important estuarine systems that are separated from the ocean by a sand beach barrier or berm. The barrier may open or close naturally because of sand and sediment movement or be manually opened by estuarine managers in times of flooding. As intermittently closed systems, it is important to understand the potential for eutrophication and what are the best indicators. This study investigated water quality, sediment quality and benthic processes in four shallow ICOLLs in Sydney, Australia, that experience a range of nutrient loadings. Manly and Curl Curl Lagoons experience higher turbidity and concentrations of pelagic Chl- a compared to Dee Why and Narrabeen Lagoons. They also differ with respect to general morphology with Manly and Narrabeen deeper and more linear while Curl Curl and Dee Why are shallower and more circular. Relationships between nutrient loading and traditional water quality indicators of eutrophication such as chlorophyll- a , turbidity and dissolved oxygen appeared to be moderated by lagoon morphology and hydrology, which control the ratio of pelagic to benthic production and net accumulation of sediment organic matter. We found that all the lagoons investigated were net heterotrophic, with Narrabeen and Manly the least and the most heterotrophic respectively. Ratios of total organic carbon (TOC):benthic community respiration (CR) varied among lagoons and were likely related to the dominance of refractory organic matter in Narrabeen (~ 99%), and more labile organic matter in Manly and Curl Curl Lagoons (~ 90%). Benthic community respiration increased with nutrient loading rates across the lagoons, suggesting that benthic processes are a critical indicator of eutrophication in these shallow systems. In contrast to the generalised conceptual model of eutrophication in coastal systems whereby nutrient pollution causes a reduction in benthic primary productivity at the expense of increased pelagic primary productivity, our results suggest that benthic microalgal productivity in shallow ICOLLs plays an important role in buffering against eutrophication of the water column but may also contribute to organic enrichment of sediments.

Assessing the ecological functioning and biodiversity of remnant native flat oyster (Ostrea angasi) reefs in temperate southeast Australia - Elisabeth M.A. Strain; Ana B. Bugnot; Boze Hancock; Robinson W. Fulweiler; Donald J. Ross; Simon E. Reeves (Marine Environmental Research, 2024)

The influence of bioturbator activity on sediment bacterial structure and function is moderated by environment - Julia Palmer; Ana B. Bugnot; Giulia Filippini; Paul E. Gribben; Deepa Varkey; Katherine Erickson; Katherine A. Dafforn (Marine Environmental Research, 2024)

Ecomorphodynamics of oyster reefs and their influence on oyster reef morphology - Francesca Roncolato; Thomas E. Fellowes; Stephanie Duce; Carolina Mora; Oskar Johansson; Indiana Strachan; Ana B. Bugnot; Katherine Erickson; Will Figueira; Paul E. Gribben; Christopher Pine; Bree Morgan; et al. (Geomorphology, 2024)

Influence of habitat features on the colonisation of native and non-indigenous species - Nina Schaefer; Melanie J. Bishop; Ana B. Bugnot; Cian Foster-Thorpe; Brett Herbert; Andrew S. Hoey; Mariana Mayer-Pinto; Shinichi Nakagawa; Craig D.H. Sherman; Maria L. Vozzo; Katherine A. Dafforn (Marine Environmental Research, 2024)

Variable effects of substrate colour and microtexture on sessile marine taxa in Australian estuaries - Nina Schaefer; Melanie J. Bishop; Ana B. Bugnot; Brett Herbert; Andrew S. Hoey; Mariana Mayer-Pinto; Craig D. H. Sherman; Cian Foster-Thorpe; Maria L. Vozzo; Katherine A. Dafforn (Biofouling, 2024)

Nitrogen-cycling genes in oyster reefs and surrounding sediments: Relationships with environmental factors and respective nitrogen rates - Giulia Filippini; Ana B. Bugnot; Deepa R. Varkey; Nachshon Siboni; Angus Ferguson; Paul E. Gribben; Katherine Erickson; Julia Palmer; Katherine A. Dafforn (Marine Pollution Bulletin, 2023)

The influence of oyster reefs and surrounding sediments on nitrogen removal – An in-situ study along the East coast of Australia - Giulia Filippini; Ana B. Bugnot; Angus Ferguson; Paul E. Gribben; Julia Palmer; Katherine Erickson; Katherine A. Dafforn (Environmental Research, 2023)

Shellfish as a bioremediation tool: A review and meta-analysis - Giulia Filippini; Katherine A. Dafforn; Ana B. Bugnot (Environmental Pollution, 2023)

Ecological impacts of two non-indigenous macroalgae on an urban rocky intertidal shore - María Gabriela Palomo; María Bagur; Marina Quiroga; Sabrina Soria; Ana Bugnot (Marine Biology, 2016)

Effects of the receiving assemblage and disturbance on the colonisation of an invasive species - Ana B. Bugnot; Ross A. Coleman; Will F. Figueira; Ezequiel M. Marzinelli (Marine Biology, 2016)

Community-level impacts of the invasive isopod Cirolana harfordi - Ana B. Bugnot; Ross A. Coleman; Will F. Figueira; Ezequiel M. Marzinelli (Biological Invasions, 2015)